Peran Guru Pendidikan Agama Islam dalam Membentuk Disiplin Shalat Berjamaah Siswa di SMK Negeri 1 Kebumen - Ismi Rizkiyanti; Maesaroh Maesaroh (IAINU Kebumen, 2026)
This study aims to examine the role of Islamic Education teachers in shaping students’ discipline in performing congregational prayers at SMK Negeri 1 Kebumen, as well as the obstacles faced and the solutions implemented by Islamic Education teachers in fostering students' discipline in congregational prayer at SMK Negeri 1 Kebumen. This research is a field study using a qualitative approach. The data were collected through observation, interviews, and documentation. The data analysis techniques used in this study include data condensation, data presentation, and conclusion drawing. The results of the study indicate that the role of Islamic Education teachers in shaping students’ discipline in performing congregational prayers at SMK Negeri 1 Kebumen includes acting as spiritual guides, role models, and motivators for students. The obstacles and solutions implemented by Islamic Education teachers in developing congregational prayer discipline include several challenges such as class schedules that are close to prayer times, the lack of awareness among some students, and limited worship facilities. The solutions applied include cooperation among teachers, mosque management, and the school administration, providing continuous motivation, and improving worship facilities